Kontribusi Generasi Muda Dalam Pertanian Indonesia - Umi Salamah (Universitas Duta Bangsa Surakarta, 2021)
Indonesia is one country that relies on the agricultural sector as its superiority. However, the need for good quality and human resources in recent years has diminished especially in the agricultural sector so that it will affect the contribution of the young agricultural / young generation workforce to the success of agriculture in Indonesia. This study aims to determine 1) the contribution of young generation agricultural sector workers in Indonesia 2) the development trend of the younger generation workforce in the agricultural sector 3) efforts to lure young people to work in the agricultural sector. The research method used is descriptive analytic method. The data used are secondary data from the Ministry of Agriculture and the Central Statistics Agency of Indonesia. The data analysis method uses the contribution method and trend line analysis. Based on the results and discussion above, it can be concluded that the value of the contribution of the agricultural youth workforce from 2014 to 2019 tends to decrease. The trendline for the development of the young agricultural workforce is y = - 518017x + 4E + 07 and is negative or will decline in the following years. Efforts to increase the interest of young people can be done in various ways such as improving education, making young entrepreneurs in agriculture and providing incentives in agriculture to attract the interest of young people working in agriculture